A Case Study on the Asymmetric Deformation Characteristics and Mechanical Behavior of Deep-Buried Tunnel in Phyllite - Chen, Ziquan; He, Chuan; Xu, Guowen; Ma, Gaoyu; Wu, Di (Rock mechanics and rock engineering, 2019)
When tunneling through deep-buried layered soft strata, asymmetric deformation of surrounding rock and asymmetric mechanical behavior of supporting structures are often encountered. This paper investigates the anisotropic mechanical properties of deep-buried carbonaceous phyllite and its influence on the asymmetrical mechanical behavior of supporting structures in the Zhegu mountain tunnel in Sichuan Province, China. It is a typical road tunnel that suffered from large asymmetrical deformation and cracking of the secondary lining due to layered strata and high geo-stresses. Firstly, experimental tests were conducted to investigate the influence of bedding angle on the mechanical properties and failure behavior of phyllite. Then, the UDEC numerical software was adopted to study the effects of the lateral pressure coefficient, rock layer inclination angle, bedding spacing and shear stress on the mechanical behavior of supporting structures. Moreover, a field test was conducted to measure the pressure between the surrounding rock and the primary support as well as the internal force of the steel arch and the secondary lining. Based on the field data and numerical simulation results, it can be concluded that the asymmetrical deformations of surrounding rock and the cracking of secondary lining in the Zhegu mountain tunnel were results of the coupling effect of layered soft rock and shearing action along the foliation.